Addressing the ice nucleating abilities of marine aerosol: A combination of deposition mode laboratory and field measurements. (May 2016) - Ladino, L.A.; Yakobi-Hancock, J.D.; Kilthau, W.P.; Mason, R.H.; Si, M.; Li, J.; Miller, L.A.; Schiller, C.L.; Huffman, J.A.; Aller, J.Y.; Knopf, D.A.; Bertram, A.K.; et al.
Abstract: This study addresses, through two types of experiments, the potential for the oceans to act as a source of atmospheric ice-nucleating particles (INPs). The INP concentration via deposition mode nucleation was measured in situ at a coastal site in British Columbia in August 2013. The INP concentration at conditions relevant to cirrus clouds (i.e.,  −40 °C and relative humidity with respect to ice, RHice  = 139%) ranged from 0.2 L −1 to 3.3 L −1 . Correlations of the INP concentrations with levels of anthropogenic tracers (i.e., CO, SO2, NOx, and black carbon) and numbers of fluorescent particles do not indicate a significant influence from anthropogenic sources or submicron bioaerosols, respectively. Additionally, the INPs measured in the deposition mode showed a poor correlation with the concentration of particles with sizes larger than 500 nm, which is in contrast with observations made in the immersion freezing mode. To investigate the nature of particles that could have acted as deposition INP, laboratory experiments with potential marine aerosol particles were conducted under the ice-nucleating conditions used in the field. At −40 °C, no deposition activity was observed with salt aerosol particles (sodium chloride and two forms of commercial sea salt: Sigma-Aldrich and Instant Ocean), particles composed of a commercial source of natural organic matter (Suwannee River humic material), or particle mixtures of sea salt and humic material. In contrast, exudates from three phytoplankton ( Thalassiosira pseudonana, Nanochloris atomus, and Emiliania huxleyi ) and one marine bacterium ( Vibrio harveyi ) exhibited INP activity at low RHice values, down to below 110%. This suggests that the INPs measured at the field site were of marine biological origins, although we cannot rule out other sources, including mineral dust. Highlights: Exudates from marine microorganisms were found to nucleate ice at cirrus conditions. The INP concentration at −40 °C and RHice  = 139% in a coastal site was below 3.3 L −1 The INPs measured at the field site were likely of marine biological origins.